2014
DOI: 10.1371/journal.pone.0097225
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Failure after Radical Surgery among Patients with Thoracic Esophageal Squamous Cell Carcinoma: Implications for the Clinical Target Volume Design of Postoperative Radiotherapy

Abstract: BackgroundThis study evaluated patterns of treatment failure (especially locoregional failure; LRF) after radical esophagectomy and proposes a clinical target volume (CTV) for postoperative radiotherapy (PORT) among patients with thoracic esophageal squamous cell carcinoma (SCC).MethodsAll patients who were followed up in our center after radical esophagectomy between 2007 and 2011 were retrospectively enrolled. The patterns of first discovered failure were assessed, and LRFs (including anastomotic and regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(96 citation statements)
references
References 23 publications
7
88
1
Order By: Relevance
“…Lymphatic recurrence was the most common pattern for patients without PRT, 87.9% in the present study. Other researches also have the same results (3,22,23). Taken in this sense, PRT should be a useful way to reduce recurrence, as sub-clinic lesions or lymphatic micrometastasis can be further controlled.…”
Section: ------------------------------------------------------------mentioning
confidence: 54%
See 1 more Smart Citation
“…Lymphatic recurrence was the most common pattern for patients without PRT, 87.9% in the present study. Other researches also have the same results (3,22,23). Taken in this sense, PRT should be a useful way to reduce recurrence, as sub-clinic lesions or lymphatic micrometastasis can be further controlled.…”
Section: ------------------------------------------------------------mentioning
confidence: 54%
“…Esophagectomy is the standard strategy for resectable EC. Unfortunately locoregional recurrence [especially lymphatic metastasis (LNM)] was the main failure for these patients (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that SCV areas were the most common site of recurrence, followed by mediastinal and abdominal areas. As such, several studies also indicated that the incidence of SCV LN recurrence was a common site of recurrence after radical surgery (range, 33.3% to 75.0%) (7)(8)(9). The available data indicates that postoperative radiotherapy could reduce locoregional recurrence and improve overall survival of ESCC patients.…”
Section: Original Articlementioning
confidence: 98%
“…Surgery alone has shown rather disappointed survival rates, which the 5-year survival rate is only 20-40%. Furthermore, approximately half of the patients may experience locoregional recurrence, which may result in a decreased survival (8,9). Various studies have suggested that the recurrences of esophageal carcinomas after radical surgery tend to occur in the bilateral supraclavicular (SCV) areas.…”
Section: Introductionmentioning
confidence: 99%
“…Frequency and distribution of nodal metastases vary greatly depending on the location, size, and depth of invasion of the primary tumor (23)(24)(25)(26)(27). The esophagus has a complex and widespread lymphatic drainage system; in addition to transmural lymphatic vessels that flow to …”
Section: Thoracic Lymphadenectomy Procedures In Radical Esophagectomymentioning
confidence: 99%